Depression and Hemoglobin levels in patients undergoing maintenance hemodialysis - Dina Simbolon; Evangeline Sitorus; Edrianne Katty Simanjuntak; Gilny Rantung (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Depression is prevalent in hemodialysis patients and may contribute to anemia, yet its impact on hemoglobin levels remains underexplored. Purpose: To examined the association between depression severity and hemoglobin levels in Indonesian hemodialysis patients. Method: A cross-sectional study was conducted at a single-site hemodialysis unit from October to December 2024. A total of 101 patients were selected using purposive sampling. Depression severity was assessed using the Beck Depression Inventory-II (BDI-II), and hemoglobin levels were measured via venous blood samples. Spearman’s correlation and linear regression analysis were used to analyze the association. Results: Depression severity was negatively correlated with hemoglobin levels (r = -0.62, p < 0.01). Patients with severe depression had hemoglobin levels nearly 3 g/dL lower than those with minimal depression. Regression analysis showed depression severity significantly predicted hemoglobin levels (Adjusted R² = 0.38, p < 0.01). Conclusion: Higher depression severity is associated with lower hemoglobin levels in hemodialysis patients. Routine mental health screening should be integrated into nephrology care, with nurses playing a key role in early detection and intervention. Future multi-center studies are needed to enhance generalizability.